UPAYA MENINGKATKAN HASIL BELAJAR IPA MENGGUNAKAN MODEL PENGAJARAN LANGSUNG SISWA KELAS V B SD NEGERI 004 BAGAN BESAR - Misnah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This classroom action research aimed to improve the science learning outcomes of fifth-grade students at SD Negeri 004 Bagan Besar Dumai through the application of a direct teaching model. The subjects of the study were students of class V B at SD Negeri 004 Bagan Besar Dumai, totaling 27 students, consisting of 16 male students and 11 female students. The parameters measured in this study included students’ learning outcomes, student activities, learning mastery, and teacher activities. The results showed that the average student learning absorption based on the daily test in cycle I reached 82.03, which was categorized as good, and increased in cycle II to an average of 93.86, categorized as very good. Individual student learning mastery in cycle I reached 85.19%, and increased to 88.89% in cycle II. Student activity in cycle I reached an average of 72.62%, categorized as sufficient, and increased in cycle II to 77.41%. Teacher activity in cycle I reached an average of 90%, categorized as good, and increased to 100% in cycle II, categorized as very good. It can be concluded that the science learning outcomes of fifth-grade students at SD Negeri 004 Bagan Besar Dumai can be improved through the application of the direct teaching model.